Effects of increasing standardized ileal digestible lysine:calorie ratio for 120- to 180-lb gilts grown in a commercial finishing environment - Shelton, N.W.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; DeRouchey, Joel M.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A 28-d growth trial was conducted to estimate the lysine requirement for 120- to 180-lb gilts. A total of 1,092 gilts (initially 121.7 lb, PIC 337 × 1050) were allotted to treatment diets with standardized ileal digestible (SID) lysine/ME ratios of 1.89, 2.12, 2.35, 2.58, 2.81, and 3.04 g/Mcal. All diets contained 0.15% L-lysine HCl and 3% choice white grease and were formulated to meet or exceed all other requirements. Seven replicate pens per treatment were used; there were approximately 26 pigs per pen. Gilts were vaccinated with 2 doses of commercial porcine circo virus type 2 (PCV2) vaccine while in the nursery. As the SID lysine content of the diet increased, both ADG and F/G improved (linear, P < 0.001) with the greatest values at the SID lysine/ME ratio of 2.58 g/Mcal. Daily SID lysine intake and SID lysine intake per pound of gain increased (linear, P < 0.001) as lysine density of the diet increased. Diet did not in-fluence (P > 0.25) feed cost per pound of gain; however, there was a tendency for improved (linear, P < 0.06) income over marginal feed cost (IOMFC) as SID lysine level increased in the diet. The SID lysine/ME ratio that yielded the greatest IOMFC value, 2.58 g/Mcal, corresponded to the treatment with the greatest growth response. On the basis of this trial, 2.58 g SID lysine/Mcal ME appears to provide the greatest biological and economical response for 120- to 180-lb gilts.
Keywords: Gilt; Lysine; Requirement